The Implementation of Maqasid Shariah in Zakat Studies - Firdausi, Shabrina Kasyifa (Islamic Social Finance, 2023)
This research aims to find out how much research on maqasid sharia and its coverage based on journals published with the theme "Maqasid Zakat". This research uses various scientific journals as data sources. By using keywords to find publications in the Dimensions database with the phrase "Maqasid Zakat". There are 132 journal articles from that have been published which is in line with the topic. Trends in publication development were used to analyze information relating to the study's subject using the bibliometric-displaying software VOSviewer by using meta-analysis technique. From the bibliometric authors mapping the author who did the most publications related to the theme "Maqasid Zakat" was Ab Rahman, Azman. There are several keywords that are classified into four clusters. In the first cluster there are 12 words that can be grouped into the theme "Sustainable Development and Poverty Alleviation". In the second cluster there are 11 words that are grouped into the theme "The Use of Zakat to Achieve Maqasid Sharia Objectives". The third cluster has 8 words related to the theme "Islamic Law and The Obligations of Muslims". The last is cluster four which consists of 1 words related to the theme "Maqasid Shariah".